The management of gastric polyps. Issue 9 (30th July 2010) - Goddard, Andrew F; Badreldin, Rawya; Pritchard, D Mark; Walker, Marjorie M; Warren, Bryan
Abstract : Background: Gastric polyps are important as some have malignant potential. If such polyps are left untreated, gastric cancer may result. The malignant potential depends on the histological type of the polyp. The literature base is relatively weak and any recommendations made must be viewed in light of this. Definition: Gastric polyps are sessile or pedunculated lesions that originate in the gastric epithelium or submucosa and protrude into the stomach lumen. Malignant potential: Depending on histological type, some gastric polyps (adenomas and hyperplastic polyps) have malignant potential and are precursors of early gastric cancer. They may also indicate an increased risk of intestinal or extra-intestinal malignancy.